2018
DOI: 10.1542/peds.2017-3918
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Release Assay Performance for Tuberculosis in Childhood

Abstract: This is the largest North American analysis of IGRA use and performance among children with TB disease. In children <5 years old, IGRA sensitivity is similar to TST, but sensitivity of both tests are reduced in children <2 years old. Indeterminate results are higher in children <1 year old and in central nervous system disease. In children ≥5 years old with laboratory-confirmed TB, IGRA has greater sensitivity than TST and should be considered the preferred immunodiagnostic test..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 35 publications
0
36
1
6
Order By: Relevance
“…In this study, the rate of indeterminate test results for children was even lower (2.2%) and was significantly lower than that for adults (5.2%). A recent study by Kay and colleagues reported an overall rate of indeterminate IGRA results of 3.7% (12 of 322 children) and found that 4 of 5 children Ͻ2 years of age with indeterminate IGRA results had central nervous system (CNS) disease, suggesting that CNS disease may be a stronger driver of indeterminate test results than age (33). In our population, only 1 of 4 children with CNS disease had an indeterminate QFT-IT result.…”
Section: Discussionmentioning
confidence: 48%
“…In this study, the rate of indeterminate test results for children was even lower (2.2%) and was significantly lower than that for adults (5.2%). A recent study by Kay and colleagues reported an overall rate of indeterminate IGRA results of 3.7% (12 of 322 children) and found that 4 of 5 children Ͻ2 years of age with indeterminate IGRA results had central nervous system (CNS) disease, suggesting that CNS disease may be a stronger driver of indeterminate test results than age (33). In our population, only 1 of 4 children with CNS disease had an indeterminate QFT-IT result.…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, the IGRA sensitivity is reduced compared to TST in children younger than 2 years old. [16] Furthermore, IGRA seems to offer alternative LTBI detection, especially babies living with TB parents. [17] This study has shown that the newborns were still negative for IGRA 12 weeks after BCG vaccination, suggesting that BCG may stimulate immune response and play a protective role against TB disease.…”
Section: Discussionmentioning
confidence: 99%
“…IFN‐γ ELISA has been developed to assess CMI in TB and is one of the IFN‐γ IGRAs used for latent tuberculosis infection diagnosis . Although the clinical performance of IGRAs varies according to the characteristics of each study, it is superior to that of the tuberculin skin test in most cases . Furthermore, IFN‐γ ELISA has already been applied for VZV CMI assessment and is a rapid and simple quantitative method with high specificity and sensitivity for direct IFN‐γ detection by using whole blood rather than peripheral blood mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…26,[40][41][42] Although the clinical performance of IGRAs varies according to the characteristics of each study, it is superior to that of the tuberculin skin test in most cases. [43][44][45][46][47] Furthermore, IFN-γ ELISA has already been applied for VZV CMI assessment 21,24,25,32 and is a rapid and simple quantitative method with high specificity and sensitivity for direct IFN-γ detection by using whole blood rather than peripheral blood mononuclear cells. In the present study, VZVspecific CMI in response to a live attenuated HZ vaccine in individuals was assessed by an IFN-γ ELISA.…”
Section: Discussionmentioning
confidence: 99%